Hotel rankings of online travel agents, channel pricing and consumer protection - Matthias Hunold; Reinhold Kesler; Ulrich Laitenberger (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We investigate whether online travel agents (OTAs) assign hotels worse positions in their search results if these set lower hotel prices at other OTAs or on their own websites. We formally characterize how an OTA can use such a strategy to reduce price differentiation across distribution channels. Our empirical analysis shows that the position of a hotel in the search results of OTAs is better when the prices charged by the hotel on other channels are higher. This is consistent with the hypothesis that OTAs alter their search results to discipline hotels for aggressive prices on competing channels, and by this reduce search quality for consumers.
Keywords: D40; L42; L81; 330; consumer protection; free-riding; hotel booking; online travel agents; ranking; search bias